Pain and Hand Functioning Differences between Guitar and Oud Students - AKEL, BURCU SEMİN (My University, 2019)
Objective: Most musicians suffer from intermittent or permanent pain which starts impairing musicians at a very early stage of music education or career. Most of the studies about instruments and musculoskeletal pain are implemented with guitar, violin or piano players. Eastern instruments are not frequently analyzed and investigated in terms of pain and discomfort. Therefore, it is aimed to investigate pain and upper extremity motor performance differences between Oud and Guitar players. Materials and Methods: Eighteen guitar players and 13 Oud players participated in the study. Pain was assessed with The Musculoskeletal Pain Intensity and Interference Questionnaire for Musicians (MPIIQM). Upper extremity motor performance was assessed with the Fine Finger Dexterity and Simulated Assembly tests of the VALPAR Work Samples. Results: The mean pain intensity score was 12,39± 11,28 whereas none of the oud players indicated any pain. The oud players' mean sub scores for the Fine Finger Dexterity were 71,42±24,82, 112,28+17,99 and 114,60+38,36 and the guitar players' mean sub-scores were 63,74+42,22, 82,09± 19,55 and 73,79± 10,29 respectively. The average Simulated Assembly score was 131,33±47,68 for oud players and 123,33+39,10 for the guitar players. The oud players' Fine Finger Dexterity scores were significantly higher than the guitar players (p=0,001 for the 1st subtest and p=0,029 for the 3rd subtest}. Also the pain intensity scores were significantly different between the groups (p=0,003). Conclusions: Oud players had higher hand functioning scores than the guitar players. Despite this fact, it was surprising that only two sub tests of Fine Motor Dexterity Test yielded significant differences. It was remarkable that the oud players did not indicate any pain whereas nearly all of the guitar players indicated moderate of high levels of pain. It was obvious that there is a significant difference between the instruments and there is a need for in-depth analysis of oud playing, training methods and of the instrument itself.